The Integration of Bugis Local Wisdom on Tolerance in Islamic Education at Senior High School: Strategies and Implications - Sultan Hasanuddin; Muhammad Rusydi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research explores the strategies and implications of integrating the value of tolerance, based on Bugis local wisdom, into Islamic religious education at SMA Negeri 1 Bone. It addresses the need for educational approaches that promote tolerance and understanding in diverse societal contexts. A qualitative research paradigm was employed, involving field research to collect data. The study focused on examining how Bugis local wisdom can be integrated into the Islamic religious education curriculum and how it can enhance teaching materials and learning media. The primary strategy identified was the integration of Bugis local wisdom values into the curriculum. This was achieved through the enrichment of teaching materials and learning media with Bugis cultural insights, alongside the reinforcement of universal values aligned with tolerance. Practical implementations included creating lesson plans, teaching aids, and media resources infused with Bugis wisdom. The findings suggest that incorporating Bugis local wisdom fosters collective awareness of diverse life phenomena, reduces arrogant behaviors among majority groups towards minorities, and promotes steps to reconcile differences, facilitating dialogue. The study emphasizes the need for detailed examples of enriched teaching materials and specific activities that promote tolerance in the classroom. It also highlights the importance of a clear theoretical framework based on existing theories of tolerance, education, and local wisdom to inform the study. Integrating Bugis local wisdom into the Islamic religious education curriculum at SMA Negeri 1 Bone effectively promotes tolerance and understanding. The study calls for further elaboration on the specific elements of Bugis wisdom incorporated and their adaptation within the educational framework to provide comprehensive insights for educators.